Profile of selected Filipino costume jewelry designers - Chu, Rudolf Carlo D.; Elumba, Patricia Santos (2008.)
The study sought to present a descriptive profile of selected local costume jewelry designers to identify the necessary qualifications that determines their success in the industry. Using purposive sampling, the respondents of this study are ten local and international design awardees, who are also entrepreneurs and acknowledged experts in the apparel accessory industry. Among the the respondents, half are Cebu-based, four of which are the founding members of Cebu Fashion Accessory Designers Guild and the rest are highly recognized Manila-based designers. A structured questionnaire was given by the researcher. The data were gathered through interviews. Questions on their personal and academic background, industry-related activities, business activities, and creative methods were asked. Analysis was done using descriptive narratives and listings in tabular format of their basic qualifications and industry experiences. Results of the study show that the Filipino costume jewelry designers are not sufficiently trained or do not have education specific on costume jewelry designing. Despite this, they were able to excel in their crafts by enriching their experiences and engaging in diverse, industry-related activities. Majority of respondents were prompted to participate in this industry because of their inclination towards the arts and the opportunities in this field. The costume jewelry designers act as product development designers and entrepreneurs. They also promote locally designed costume jewelry through their marketing networks and industry affiliations. The researcher recommends that a further study be done on the business side of costume jewelry design and production. That includes more discussions on the business aspect of this study in order to gain more knowledge and understanding of the requirements for success in the costume jewelry industry.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Jewelry making -- Philippines; Designers -- Philippines